Implementasi Pendidikan Karakter Dalam Kurikulum 2013 Terhadap Siswa Kelas III Di MI NU Tebat Jaya - Eva Widayanti; Tri Ratna Dewi2; Sri Enggar Kencana Dewi3 (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to determine character values in the 2013 Curriculum, to determine the implementation of character education in the 2013 Curriculum and to determine the supporting factors and inhibiting factors for the implementation of student character values in the 2013 Curriculum. in Tebat Jaya Village, Buay Madang District, Ogan Komering Ulu Timur Regency. By using descriptive qualitative research methods and data collection techniques through interviews, observation and documentation. Data analysis techniques used in this study are data reduction, data presentation, and conclusion drawing. The results of this study indicate that the development of character values that have been implemented by MI NU Tebat Jaya in the 2013 curriculum include: Religious, Honest, Disciplined and Responsible. The implementation of character education in the 2013 curriculum carried out by students, especially grade III students at MI NU Tebat Jaya has been going well in accordance with the rules in the 2013 curriculum. rules, teachers and parents who care and always motivate children's character, as well as adequate school facilities. While the inhibiting factors are different student backgrounds, lack of parental care, less binding rules, and the influence of the surrounding environment in terms of association to face the progress of the globalization era.